Memories of a young student: the early days of splicing regulation with François Gros - Libri, Domenico (Comptes Rendus Biologies)
I joined the laboratory of François Gros as a young student in the mid-1980s and worked on the characterization of the $β $-tropomyosin gene in chicken and the regulation of alternative splicing of its transcript, under the supervision of Marc Fiszman. In particular, I was interested in how secondary structures of the RNA influence the recognition of exons specifically used in muscle cells. I will recall a few memories on how interacting with François on this project shaped my perception of the scientific process and of the relationships between models and data. Later I worked on many aspects of RNA biology, from transcription to mRNP biogenesis and non-coding RNAs.